2014 IEEE 64th Electronic Components and Technology Conference (ECTC) 2014
DOI: 10.1109/ectc.2014.6897489
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional system integration in flexible substrates

Abstract: In this paper we present a technology developed for reliable electrical interconnection on film substrates and between vertically stacked film layers. Applying through-hole via technologies for 3D foil stacks enables multi-functionality and RF performance combined with open form-factor and very cost-efficient manufacturing of conformable electronic modules. The manufacture of fine line metal patterns (line /space geometries below 20μm) on film substrates is performed by cost-effective roll-to-roll technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Polyimide, as well as BCB, can be applied by spin coating, resulting in thin layers with homogenous thicknesses [ 13 , 14 , 15 ]. Openings in the polymeric layer can be established by laser drilling [ 10 , 16 , 17 , 18 , 19 ] or photolithography [ 20 , 21 , 22 ]. Afterwards, conductive tracks are applied.…”
Section: Introductionmentioning
confidence: 99%
“…Polyimide, as well as BCB, can be applied by spin coating, resulting in thin layers with homogenous thicknesses [ 13 , 14 , 15 ]. Openings in the polymeric layer can be established by laser drilling [ 10 , 16 , 17 , 18 , 19 ] or photolithography [ 20 , 21 , 22 ]. Afterwards, conductive tracks are applied.…”
Section: Introductionmentioning
confidence: 99%
“…After silicon thinning, the chips are detached from the wafer release foil and assembled either by face-down flip-chip technology [ 9 , 10 , 11 ] or face-up die-bonding with subsequent electrical contacting [ 12 , 13 , 14 , 15 ]. There are various disadvantages of flip-chip assembly in regard to ultrathin chips.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of organic and inorganic electronics on bendable substrates and plastic foils are discussed in both [29] and [30]. In these studies electronic performance was observed to decrease at a bending radius of 5mm; resistivity at the same bending radius only changed by 5% [29]. Piezoelectric flexible tactile sensors printed on ultrathin polyimide were constructed in [31].…”
Section: Robot Skin Manufacturing Technologymentioning
confidence: 99%